A Bibliometric Analysis of 15 Years of Research on Open Educational Resources (International Conference on Computers in Education, 2017)
Open educational resources (OER) has developed for fifteen years since the term was adopted for the first time in 2002. To explore its research development progress as well as research focuses, this study reviewed literature on OER from the year of 2002 to 2017 with a bibliometric method based on seven indicators including publication year, distribution by country/territory, distribution by institution, journals, authors, essays and keywords. The findings include: 1. the top five productive countries of OER related research consist of Spain, USA, England, Romania, and China, 2. geographic proximity is a predominant factor in co- authorships, 3. International Review of Research in Open and Distance Learning is the most influential journal in the field of OER, 4. UK Open University is the most productive institution, 5. the research hot spots include OER, e-learning, higher education, mooc, open access, teacher training, ICT and open textbooks, innovation, pedagogy, web 2.0, etc., 6. there are three stages of OER research: emergence stage (2002-2007), exploration stage (2008-2011) and application stage (2012-2017), 7. policy and funding are two crucial factors influencing OER movement, and 8. sustainability, copyright, higher education, MOOCs are worthy of researchers’ attention. Hopefully this essay could draw a full picture of existing OER research, indicate its progress and frontiers, as well as provide implications for future work.